Musical Work as the Object of Copyright and Related Rights - Ibrokhimov Azimjon Abdumomin ogli (Genius Journals, 2023)
This article examines the importance of copyright and related rights in protecting and promoting musical works. Musical works, encompassing compositions and compositions with lyrics, hold significant cultural and economic value, necessitating legal frameworks to safeguard the rights of creators and foster a thriving music industry. The article explores the scope of copyright protection, including reproduction, distribution, public performance, and adaptation rights, which grant creators exclusive control over their works. It also addresses the duration of copyright protection and the transition of works into the public domain. Furthermore, the article discusses related rights granted to performers, sound recording producers, and broadcasting organizations. The research methods employed include literature reviews, legal analysis, case studies, industry reports, and expert opinions. By drawing on these sources, the article provides a comprehensive understanding of the complexities and implications of copyright in relation to musical works. Ultimately, the article underscores the significance of copyright and related rights in nurturing creativity, rewarding artistic endeavors, and sustaining a vibrant music landscape in the digital age
Keywords: musical work; copyright; related rights